Protected Areas in the Brazilian Semi-Arid and the Management and Conservation of Ecosystems - Pacheco, Clecia Simone G. R.; Santos, Reinaldo Pacheco dos; Araújo, Izabel P. R. de (International Journal of Environment, Agriculture and Biotechnology, 2019)
The use of biodiversity has not been done sustainably on the planet, especially in South America, which has caused irreversible environmental impacts. Geodiversity is an important component of the existing natural heritage, but it lacks studies that mainly exploit the characteristics of the landscape and its forms of conservation. In this way, the aim is to discuss the relevance of the sustainable use of natural resources of protected areas of the Brazilian semi-arid, especially of the paleodunate areas, as well as to present a proposal for the management and conservation of these areas in accordance with the realities investigated, based on renowned theorists, in the existing legislations and above all, based on the practical investigations carried out. Therefore, it is crucial to understand the relevance of the adequate management of Brazil's protected areas, especially those that have environmental indicators from other geological eras and that, once destroyed, will never be recomposed, since it is a dynamic complex, thus requiring greater attention and a coherent management for its actual conservation.